NGS in the clinical microbiology settings - Pitashny, Milena; Kadry, Balqees; Shalaginov, Raya; Gazit, Liat; Zohar, Yaniv; Szwarcwort, Moran; Stabholz, Yoav; Paul, Mical (Frontiers in Cellular and Infection Microbiology, 2022)
We hypothesized that targeted NGS sequencing might have an advantage over Sanger sequencing, especially in polymicrobial infections. The study included 55 specimens from 51 patients. We compared targeted NGS to Sanger sequencing in clinical samples submitted for Sanger sequencing. The overall concordance rate was 58% (32/55) for NGS vs. Sanger. NGS identified 9 polymicrobial and 2 monomicrobial infections among 19 Sanger-negative samples and 8 polymicrobial infections in 11 samples where a 16S gene was identified by gel electrophoresis, but could not be mapped to an identified pathogen by Sanger. We estimated that NGS could have contributed to patient management in 6/18 evaluated patients and thus has an advantage over Sanger sequencing in certain polymicrobial infections.